The Relationship Between High-Level Violin Performers' Movement and Evaluators' Perception of Musicality. Issue 1 (July 2019) - Bugaj, Katarzyna A.; Mick, James; Darrow, Alice-Ann
The purpose of this study was to examine possible relationships between the extent of high-level violin performers' movement during performance and evaluators' perceptions of their musicality. Stimuli were 10 excerpts of solo violin performances from the 2015 Tadeusz Wronski International Violin Competition for Solo Violin, selected to convey high and low amounts of performer movement. Participants were undergraduate music majors ( N = 274) divided into three groups by experimental conditions: visual-only ( n = 109), audio-only ( n = 78), or audio-visual ( n = 87). Analysis demonstrated that performers exhibiting high movement were perceived as more musical than performers exhibiting low movement. The findings suggest that even accomplished musicians are subject to evaluation biases based on stage presence and physical behaviors such as movement.